ANNA'S CULTURE SHOCK EXPERIENCES IN THE ANNA AND THE KING MOVIE - Hersya Septita Rosady; Inti Englishtina (LINGUAMEDIA Journal, 2023)
This thesis is a study of the cultural shock experienced by the main character in the movie Anna and The King using the theory of general culture shock from Oberg (1960) to support the writing. The purpose of the study is (1) to describe the phases of process of cultural shock experienced by Anna in Anna and the King movie (2) To show the evidence and effects of culture shock experienced by character in Anna and the King Movie. The method used in this research is descriptive qualitative method. Data of this research is taken from the film; the scripts and the scenes are used as references to analyze the data and support for this research. In this research, the writer found through culture shock phases stages of culture shock, the evidence and the effect experienced by the main character. The culture shock phases are honeymoon, crisis, recovery, and adjustment. Then the writer also found the effects of culture shock based on the four phases above. There are two effects of culture shock. The positive effects include culture shock gives us new knowledge about culture, culture shock can make friends from all over the world, culture shock builds confidence, get to know a new language. The negative effects include anxiety, confusion, homesickness or anger. The conclusion of the research described the phases the evidence and the effect of culture shock by Oberg’s Theory that can give information to the readers or the next researchers.Key words: Culture, culture shock, film, literature, cultural differences